Extractability and mobility of mercury from agricultural soils surrounding industrial and mining contaminated areas - Reis, Ana Teresa; Rodrigues, Sónia Morais; Davidson, Christine M.; Pereira, Eduarda; Duarte, Armando C. (Chemosphere (Oxford), 2010)
This study focussed on a comparison of the extractability of mercury in soils with two different contamination sources (a chlor-alkali plant and mining activities) and on the evaluation of the influence of specific soil properties on the behaviour of the contaminant. The method applied here did not target the identification of individual species, but instead provided information concerning the mobility of mercury species in soil. Mercury fractions were classified as mobile, semi-mobile and non-mobile. The fractionation study revealed that in all samples mercury was mainly present in the semi-mobile phase (between 63% and 97%). The highest mercury mobility (2.7 mg kg −1) was found in soils from the industrial area. Mining soils exhibited higher percentage of non-mobile mercury, up to 35%, due to their elevated sulfur content. Results of factor analysis indicate that the presence of mercury in the mobile phase could be related to manganese and aluminium soil contents. A positive relation between mercury in the semi-mobile fraction and the aluminium content was also observed. By contrary, organic matter and sulfur contents contributed to mercury retention in the soil matrix reducing the mobility of the metal. Despite known limitations of sequential extraction procedures, the methodology applied in this study for the fractionation of mercury in contaminated soil samples provided relevant information on mercury’s relative mobility.